A case study of learning assessment, flow, satisfaction and expressiveness of the music game: focused on elementary students' music appreciation learning. (2016) - Park, Seungie; Rhee, Dae-Woong; Kihl, Taesuk
This study examines the effectiveness of a music game for music appreciation education on learners' learning assessment, learning flow, satisfaction, and expressiveness of elementary students. For the experiment, fourth grade students were divided into two groups; listening group and game group. Game group played a music game which was designed for music appreciation while the listening group listened to the music following lecture's instructions. Pre- and post-measurements of learning assessment were taken to compare the music appreciation scores between the groups. In the post-measurement, learning flow, satisfaction, and expression of music works were added. As a result, the students in the game group showed more enhanced learning assessment, learning flow, and satisfaction than those in the listening group and especially in terms of expressiveness they showed imaginative expression in their drawings or writings. The following result suggests that learning through game-playing have positive effect on students' self-directed learning and expressiveness.